A lab-scale anoxic/oxic-bioelectrochemical reactor for leachate treatments. (June 2015) - Zhang, Guodong; Jiao, Yan; Lee, Duu-Jong
Highlights: Liter-scale membraneless BES with biocathode was setup for leachate treatment. Anoxic/oxic (A/O) zones connected with a reflux facilitate nitrogen removal. With raw landfill leachate, the BES reached >90% COD and NH4 + –N removal. The species in biofilms support the functions of the A/O-BES. Abstract: A membraneless, liter-scale bioelectrochemical reactor with both bioanode and biocathode was established for landfill leachate treatment. Anoxic/oxic (A/O) zones at anode compartment and cathode compartment, respectively, were connected with a reflux to facilitate nitrogen removal. With raw landfill leachate of 17, 500–22, 600 mg L −1 chemical oxygen demand (COD) and 1170–1490 mg L −1 NH4 + –N, the tested reactor removed 89.1 ± 1.6% of chemical oxygen demand and 99.2 ± 0.1% of NH4 + –N at 3.0 kg COD m −3  d −1 . The corresponding maximum power density was 2.71 ± 0.09 W m −3, with internal resistance of 46.7 ± 1.6 Ω and open circuit voltage of 727 ± 7 mV. The species of Pseudomonas, Desulfovibrio, Bacillus, Enterococcus, Pelospora, Dehalobacter dominated the anodic community, while those of methylotrophs, Rhodobacter, Verrucomicrobiaceae, Geobacter, Flavobacterium, Thauera, Desulfovibrio and Aeromonas dominated the cathodic community. The proposed A/O bioelectrochemical reactor is a prototype for practical treatment of landfill leachate at affordable costs.